2003
DOI: 10.1097/01.ccm.0000089939.11032.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different inspiratory rise time and cycling off criteria during pressure support ventilation in patients recovering from acute lung injury

Abstract: Our results suggest that in patients recovering from acute lung injury during pressure support ventilation, a) the shortest inspiratory rise time reduces the WOBI; and b) at 15 cm H2O of pressure support ventilation, the lowest cycling off criteria reduces the respiratory rate and increases the tidal volume without modifying the WOBI and WOBE. Modifications of inspiratory rise time and cycling off criteria must be carefully adjusted during pressure support ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 24 publications
4
47
1
4
Order By: Relevance
“…At f 30 and f 40 , the helmet had a shorter mechanical T I than the ETT and face mask (P Ͻ .01), whereas at f 50 , the face mask had the longest mechanical T I compared with the ETT and helmet (P Ͻ .05).…”
Section: Pediatric Model With a Mixed Obstructive And Restricted Respmentioning
confidence: 95%
See 3 more Smart Citations
“…At f 30 and f 40 , the helmet had a shorter mechanical T I than the ETT and face mask (P Ͻ .01), whereas at f 50 , the face mask had the longest mechanical T I compared with the ETT and helmet (P Ͻ .05).…”
Section: Pediatric Model With a Mixed Obstructive And Restricted Respmentioning
confidence: 95%
“…At f 30 and f 40 , the helmet presented the shortest mechanical T I /T tot compared with the ETT and face mask (P Ͻ .05), but at f 50 , the face mask had a shorter ratio than the other interfaces (P Ͻ .01).…”
Section: Pediatric Model With a Mixed Obstructive And Restricted Respmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Cycle criteria are also expected to influence inspiratory duration and may possibly decrease LI-RAP. 8,14,15 Our simulation study revealed that changes in cycle criteria could affect the duration and magnitude of LIRAP in various lung models but could abolish LIRAP only in restrictive lung model when inspiratory effort is medium to high. lung model only.…”
Section: Discussionmentioning
confidence: 99%